Modelagem geológica e geofísica 2,5-D de estruturas geológicas complexas tipo pré-sal:exemplo sintético - BARBOSA, Ray Diego de Lima (2019)
There are areas that present in the subsurface terrestrial complex geological structures (eg. faults, salt domes, dykes, folds, and diabase sills) that reduce the quality of seismic imaging, providing false images as a result of the geological structures under investigation. In rock structures called pre-salt, where the reservoirs can be found between 5.300me 7000m deep below a thick salt layer that acts as a seal, the modeling and visualization technologies can be used to minimize the risk exploratory oil and gas as well as to check the different topologies of complex structures, construction of maps, cross sections, correlation of wells, channel simulation, geological interpretation, 3D modeling (model stratigraphic model Gear, tanks, basins, surfaces with arbitrary topologies), and so on. In this paper we used the modeling tool 2.5 D with the goal of modeling complex geological structures in the pre-salt. The models were the models structural, stratigraphic, and speed. For the construction of these models were considered geological sections, and seismic (actual data) of sedimentary basins where there are structures present in the pre-salt. In this model there is the presence of a petroleum system understood in this region. These structures may be part of sedimentary basins and be located in areas with adequate structures for hydrocarbon accumulation.